If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(2 + -1x) = -2(2x + -4) x + (2 * -1 + -1x * -1) = -2(2x + -4) x + (-2 + 1x) = -2(2x + -4) Reorder the terms: -2 + x + 1x = -2(2x + -4) Combine like terms: x + 1x = 2x -2 + 2x = -2(2x + -4) Reorder the terms: -2 + 2x = -2(-4 + 2x) -2 + 2x = (-4 * -2 + 2x * -2) -2 + 2x = (8 + -4x) Solving -2 + 2x = 8 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -2 + 2x + 4x = 8 + -4x + 4x Combine like terms: 2x + 4x = 6x -2 + 6x = 8 + -4x + 4x Combine like terms: -4x + 4x = 0 -2 + 6x = 8 + 0 -2 + 6x = 8 Add '2' to each side of the equation. -2 + 2 + 6x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + 6x = 8 + 2 6x = 8 + 2 Combine like terms: 8 + 2 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| 9z^2-9z-9=0 | | y^2=y+12 | | n/6+48=62 | | 20+8x-5=8x+21 | | 8000+8000(.20-x)=7200 | | 59=7+4m | | 10x-5=25whatx | | -5x^2+450x-10000=0 | | -5x-3y=12 | | -10y+18=-15y-2+5y | | 5x+10-10=30 | | x^2-5xy+y^2=4 | | 3x-6=6x-36 | | 11x+16=6x+81 | | (2y+1)/4=(y-3)/3 | | (2y+1)/4=(y-3)/3 | | 4x/2x^2 | | 7k-(9k-16)=14-(19-k) | | x^2+xy=5 | | 8x-4=17+x | | ax-7a=1 | | 0.6-50y=3 | | x+3+8x=5x-12 | | (4x+2)/3+x/8=6 | | 1+ln(x)=0 | | 5x-22=-3x+2 | | n^2+1n-56=0 | | 6x^2+5x=25 | | 2x^4-x^2-28=0 | | 13=2m+12-19 | | 4x+2/3=6 | | 22a+8b-3a-2b= |